REMOVAL OF REACTIVE VIOLET 5 DYES USING OZONE-BASED ADVANCED OXIDATION PROCESS (AOP) WITH ACTIVATED CARBON AND UV LIGHT AS CATALYST - Kurnia Putri Utami, Rahmadhani
Every year, the textile industry discharges liquid waste with low biodegradability level into water bodies in large quantities. This low biodegradability is caused by the presence of refractory compounds, a few of those are azo compounds. These azo compounds come from residues of used dye during the textile dyeing process. Azo is found in dyes in the form of chromophore group, such as in Reactive Violet 5 dye (RV5) which has one azo chromophore. Conventional process has difficulties on degrading these azo compounds. To overcome this problem, Advanced Oxidation Process (AOP) was introduced. AOP utilizes hydroxyl radicals with high oxidation potential, to effectively remove azo compounds. In order to increase the production of hydroxyl radicals, several types of catalysts, such as homogeneous, heterogeneous and photocatalysts, are used. The aim and objective of this research is to analyze and to compare the removal of RV5 using two variations of catalyst, activated carbon (heterogenous catalyst) and UV light radiation (photocatalyst). Success indicators depends on the efficiency of color and organic compounds removal. This study also includes the influence of other experimental parameters such as initial RV5 concentration, initial pH, and catalyst dosage. The results showed that the most effective removal of RV5 was carried out at pH 11. The addition of 3 grams/L of activated carbon in the experiment with high initial waste concentration of (100 mg/L RV5 + 100 mg/L glucose) was able to increase the efficiency of color and organic compounds removal through the catalytic ozonation and adsorption up to 99% and 70%. Meanwhile, the combination with UV light radiation was able to increase the removal efficiency of color and organic compounds by 95% and 48% respectively.